(untitled) (Journal of Pakistan Orthopaedic Association, 2016)
Objective: Evaluation of antibiotic cement impregnated nailing in the management of infected non-union of femur. Methods: The prospective study was made on 19 cases of infected non-union of femur from 2014 to 2015 Evaluation of functional outcomes was made in reference with controlling of infection and bony union. Results: Eradication of infection was achieved in 14 cases with antibiotic cement impregnated intramedullary nail (ACIIN) and the fractures united. Despite of the fact that control over infection with ACIIN was noted but successive measures were adopted for achievement of bony union in three cases. One had union in presence of infection while one persisted with infected non-union. Conclusion: Antibiotic cement impregnated nailing is an effective, very economic and easy technique than that of conventional techniques for managing infected non-unions of long bones. Keywords: Long bones, antibiotic cement impregnated nail, Infected non-union